Optic flow informs distance but not profitability for honeybees - Shafir, Sharoni (The Royal Society, 2010)
How do flying insects monitor foraging efficiency? Honeybees (Apis mellifera) use optic flow information as an odometer to estimate distance travelled, but here we tested whether optic flow informs estimation of foraging costs also. Bees were trained to feeders in flight tunnels such that bees experienced the greatest optic flow en route to the feeder closest to the hive. Analyses of dance communication showed that, as expected, bees indicated the close feeder as being further, but they also indicated this feeder as the more profitable, and preferentially visited this feeder when given a choice. We show that honeybee estimates of foraging cost are not reliant on optic flow information. Rather, bees can assess distance and profitability independently and signal these aspects as separate elements of their dances. The optic flow signal is sensitive to the nature of the environment travelled by the bee, and is therefore not a good index of flight energetic costs, but it provides a good indication of distance travelled for purpose of navigation and communication, as long as the dancer and recruit travel similar routes. This study suggests an adaptive dual processing system in honeybees for communicating and navigating distance flown and for evaluating its energetic costs.